DFT Study on the Interaction of Lenalidomide Anticancer Drug on the Surface of B12N12 Nanocluster - Sharifi, Shamsa; Sheikhi, Masoome; Shahab, Siyamak; Kaviani, Sadegh; Kumar, Rakesh (Letters in Organic Chemistry, 2022)
The adsorption of the Lenalidomide (LNA) drug on the surface of the B12N12 nanocluster has been studied using DFT and TD-DFT calculations. The quantum calculations have been performed at the B3LYP/6-311+G** level of theory in the solvent water. The change of DM also displays a charge transfer between LNA and nanocluster. The adsorption of the LNA drug from the O1 atom on the B12N12 nanocluster leads to higher electrical conductivity due to the low Eg rather than the other active sites. According to QTAIM analysis, -G(r)/V(r) values for B-O and B-N bonds are between 0.5 and 1, confirming the partially covalent character. The values of LOL and ELF are low in the region between the nitrogen and oxygen atoms of LAN and B12N12, which show that the interactions have mainly non-covalent character. The calculated data revealed that the B12N12 nanocluster can be an appropriate biomedical carrier for the delivery of LNA drugs.
Keywords: Lenalidomide